UEDGE-CRUMPET predicted isotopologue effect on atomic and molecular emission in DIII-D high-recycling divertor plasmas. (March 2023) - Holm, Andreas; Groth, Mathias; McLean, Adam; Scotti, Filippo; Rognlien, Thomas D.; Meyer, William H.; Shafer, Morgan W.; Wilcox, Robert S.; Hollmann, Eric M.
Abstract: UEDGE-CRUMPET simulations indicate the impact of the molecular hydrogenic isotopologue effect under high-recycling LFS divertor conditions in DIII-D to be negligible for electron density and temperature profiles at the LFS target plate. A 30% decrease in molecular content, accompanied by a 10% increase in atomic content, is predicted for deuterium compared to hydrogen. The predicted isotopologue effect on the radiative power balance, validated with calibrated spectroscopy, is found to be small despite a 20% increase in LFS divertor molecular band emission for deuterium compared to hydrogen. The predictions and measurements show a negligible contribution of molecularly-induced atomic and direct molecular emission to the total radiative power balance under high-recycling conditions, consistent with previous EDGE2D-EIRENE investigations. The UEDGE-CRUMPET simulations were performed using effective hydrogen and deuterium rates considering molecular breakup and excitation processes for H 2 and D 2, calculated by the CRUMPET collisional-radiative model. Highlights: The hydrogenic isotopologue effect is negligible under high-recycling conditions A 20% isotopologue-related increase in molecular content predicted under detachment The predicted isotopologue effect on the radiative power balance is found to be small Molecularly-induced radiation is significant under detached conditions